Effects of organic strength on performance of microbial electrolysis cell fed with hydrothermal liquefied wastewater - Ruixia, Shen; Jianwen, Lu; Zhangbing, Zhu; Na, Duan; Haifeng, Lu; Zhang, Yuanhui; Zhidan, Liu (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Microbial electrochemical technology has drawn increasing attention for the treatment of recalcitrant wastewater as well as production of energy or value-added chemicals recently. However, the study on the treatment of hydrothermal liquefied wastewater (HTL-WW) using microbial electrolysis cell (MEC) is still in its infancy. This study focused on the effect of organic loading rates (OLRs) on the treatment efficiency of recalcitrant HTL-WW and hydrogen production via the MEC. In general, the chemical oxygen demand (COD) removal rate was more than 71.74% at different initial OLRs. Specially, up to 83.84% of COD removal rate was achieved and the volatile fatty acids were almost degraded at the initial OLR of 2 g COD/L•d in the anode of MEC. The maximum hydrogen production rate was 3.92 mL/L•d in MEC cathode, corresponding to a hydrogen content of 7.10% at the initial OLR of 2 g COD/L•d. And in the anode, the maximum methane production rate of 826.87 mL/L•d was reached with its content of 54.75% at the initial OLR of 10 g COD/L•d. Analysis of electrochemical properties showed that the highest open circuit voltage of 0.48 V was obtained at the initial OLR of 10 g COD/L•d, and the maximum power density (1546.22 mW/m3) as well as the maximum coulombic efficiency (6.01%) were obtained at the initial OLR of 8 g COD/L•d. GC-MS analysis revealed the existence of phenols and heterocyclic matters in the HTL-WW, such as 1-acetoxynonadecane and 2,4-bis(1-phenylethyl)-phenol. These recalcitrant compounds in HTL-WW were efficiently removed via MEC, which was probably due to the combination effect of microbial community and electrochemistry in MEC anode.Keywords: microbial electrolysis cell, corn stover, hydrothermal liquefaction, recalcitrant wastewater, hydrogen production, organic strengthDOI: 10.3965/j.ijabe.20171003.2879Citation: Shen R X, Lu J W, Zhu Z B, Duan N, Lu H F, Zhang Y H, et al. Effects of organic strength on performance of microbial electrolysis cell fed with hydrothermal liquefied wastewater. Int J Agric & Biol Eng, 2017; 10(3): 206–217.